Product Diversification in The Furniture Industry in Tanjung Anom Village, Deli Serdang - Muhdi, Muhdi; Hanafiah, Diana Sofia (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Furniture industry is experiencing a shift towards multifunctional furniture products due to additional flexibility, functionality and smaller sizes. The output target to be achieved from this community service activity is the achievement of community independence and technology transfer in producing furniture in Tanjung Anom Village, Deli Serdang. Utilization and allocation of wood processing machines for furniture will affect productivity and work performance in furniture manufacturing at UD Jaya Bersama in Tanjung Anom Village, Deli Serdang. Using sawmills at UD Jaya Bersama, the average productivity is 3 days higher than the labor-intensive system, which is 5 days to manufacture a set of tables and chairs. This shows that the use of wood processing machines at UD Jaya Bersama is more efficient. The products produced at UD Jaya Bersama in Tanjung Anom Village, Deli Serdang are sills, doors, windows, cupboards, LCD cases, tables and chairs. Manufacture and sale of products is still based on consumer orders. Product pricing at UD Jaya Bersama in Tanjung Anom Village, Deli Serdang depends on the raw material used, namely the type of wood. The raw materials used come from Intsia spp., Agathis dammara, and Shorea spp.